The Effect of Earning Per Share and Cash Flow of Operating on Stock Prices - Muhammad Ilham Ramadhani (Perkumpulan Praktisi Akuntansi Indonesia, 2022)
The company is an entity that aims to seek profit for the welfare of the owner. Achieving company profits requires resources in carrying out its business processes. One of the resources that companies really need is funds. Companies can raise funds in various ways, one of which is by issuing securities such as shares on the stock exchange. Stock is an investment that has a big risk so that investors need to consider more to invest in stocks, one of which is by considering the earnings per share and the company's cash earning ability in the company's main activities. So as to know the effect of earnings per share and operating cash flow on stock prices. If earnings per share and operating cash flow are attractive to investors, the demand for shares in the company will increase, causing share prices to rise. Therefore, a regression test is conducted to determine the effect of earnings per share and operating cash flow on stock prices, the results are that earnings per share and operating cash flow have a significant effect on stock prices, these results are supported by previous research results which has the same test result.